2018
DOI: 10.1002/gps.4933
|View full text |Cite
|
Sign up to set email alerts
|

Course of neuropsychiatric symptoms in dementia: 5‐year longitudinal study

Abstract: Severe NPS are already common at time of dementia diagnosis, and the increase in overall severity over 5 years was moderate. Individual symptoms tend to fluctuate over time within patients and correspond to states rather than traits. These findings highlight the need to focus on, and plan for, NPS as part of dementia pathway, and are relevant for clinical trial design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
75
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 39 publications
4
75
0
2
Order By: Relevance
“…(i.e., executive function impairment, decreased mobility, motor and non-motor symptoms, psychiatric and autonomous symptoms) and due to the consequences of these manifestations (poor adherence and adverse effects to medications, polypharmacy, worsening of comorbidities, need for care, falls, geriatric syndromes, among others) [24]. Our research group has previously reported high mortality in DLB, which we can now infer, may be associated with the high prevalence of frailty [25]. …”
Section: Discussionmentioning
confidence: 99%
“…(i.e., executive function impairment, decreased mobility, motor and non-motor symptoms, psychiatric and autonomous symptoms) and due to the consequences of these manifestations (poor adherence and adverse effects to medications, polypharmacy, worsening of comorbidities, need for care, falls, geriatric syndromes, among others) [24]. Our research group has previously reported high mortality in DLB, which we can now infer, may be associated with the high prevalence of frailty [25]. …”
Section: Discussionmentioning
confidence: 99%
“…16 Understanding the effect of individual NPSs on carer distress is of great clinical importance in terms of identifying carers at risk of stress-related health problems and identifying the support needs of families dealing with dementia. 16 Understanding the effect of individual NPSs on carer distress is of great clinical importance in terms of identifying carers at risk of stress-related health problems and identifying the support needs of families dealing with dementia.…”
Section: The Association Between Individual Npss and Carer Distressmentioning
confidence: 99%
“…NPSs 16. For example, this study identifies sleep and nighttime disturbances, which are core clinical features of DLB, as important contributors to distress in the DLB group, both in the PLS regression model and in the correlation analysis.…”
mentioning
confidence: 92%
See 2 more Smart Citations